Pathogenic LRRK2 variants are gain-of-function mutations that enhance LRRK2-mediated repression of β-catenin signaling. Issue 1 (December 2017) - Berwick, Daniel; Javaheri, Behzad; Wetzel, Andrea; Hopkinson, Mark; Nixon-Abell, Jonathon; Grannò, Simone; Pitsillides, Andrew; Harvey, Kirsten
Abstract Background LRRK2 mutations and risk variants increase susceptibility to inherited and idiopathic Parkinson's disease, while recent studies have identified potential protective variants. This, and the fact that LRRK2 mutation carriers develop symptoms and brain pathology almost indistinguishable from idiopathic Parkinson's disease, has led to enormous interest in this protein. LRRK2 has been implicated in a range of cellular events, but key among them is canonical Wnt signalling, which results in increased levels of transcriptionally active β-catenin. This pathway is critical for the development and survival of the midbrain dopaminergic neurones typically lost in Parkinson's disease. Methods Here we useLrrk2 knockout mice and fibroblasts to investigate the effect of loss of Lrrk2 on canonical Wnt signalling in vitro and in vivo. Micro-computed tomography was used to study predicted tibial strength, while pulldown assays were employed to measure brain β-catenin levels. A combination of luciferase assays, immunofluorescence and co-immunoprecipitation were performed to measure canonical Wnt activity and investigate the relationship between LRRK2 and β-catenin. TOPflash assays are also used to study the effects of LRRK2 kinase inhibition and pathogenic and protectiveLRRK2 mutations on Wnt signalling. Data were tested by Analysis of Variance. Results Loss of Lrrk2 causes a dose-dependent increase in the levels of transcriptionally active β-catenin in the brain, and alters tibial bone architecture, decreasing the predicted risk of fracture.Lrrk2 knockout cells display increased TOPflash andAxin 2 promoter activities, both basally and following Wnt activation. Consistently, over-expressed LRRK2 was found to bind β-catenin and repress TOPflash activation. Some pathogenic LRRK2 mutations and risk variants further suppressed TOPflash, whereas the protective R1398H variant increased Wnt signalling activity. LRRK2 kinase inhibitors affected canonical Wnt signalling differently due to off-targeting; however, specific LRRK2 inhibition reduced canonical Wnt signalling similarly to pathogenic mutations. Conclusions Loss of LRRK2 causes increased canonical Wnt activity in vitro and in vivo. In agreement, over-expressed LRRK2 binds and represses β-catenin, suggesting LRRK2 may act as part of the β-catenin destruction complex. Since some pathogenicLRRK2 mutations enhance this effect while the protective R1398H variant relieves it, our data strengthen the notion that decreased canonical Wnt activity is central to Parkinson's disease pathogenesis.